KNOWLEDGE AND ATTITUDES OF HEALTH WORKERS TOWARDS COVID-19 VACCINATION IN ACEH, INDONESIA - Riyan Arisandi; Budi Yanti; Iskandar Zakaria (Indonesian Journal of Health Administration, 2023)
Introduction: Herd immunity through vaccination is one of the major strategies for overcoming the COVID-19 pandemic, but there are still doubts about vaccines among health workers. Aims: This study aims to assess the relationship between knowledge of the COVID-19 vaccine and the attitudes of health workers. Methods: This is a cross-sectional study, which involves the distribution of a validated online questionnaire through Google Forms to health workers at Zainoel Abidin General Hospital Banda Aceh. The data consist of general characteristics, 13 questions regarding knowledge, and nine inquiries related to attitudes. Results: There were 301 respondents, of which 87.4% were females and 48.8% were nurses. Only 27.9% of the health workers have a history of COVID-19 courses, 67.8% have good knowledge about the vaccine, and 70.8% with a positive attitude. There was a significant relationship between the knowledge of the vaccine and health workers' attitudes. Furthermore, gender, age, education level, and training history did not affect the knowledge of vaccination, while profession was the main influential factor. Conclusion: This study shows that there is a relationship between knowledge of the COVID-19 vaccine and health workers' attitudes. However, stakeholders must always focus on strategies that can increase understanding and practice of disease prevention Keywords: attitude, COVID-19 vaccine, knowledge, health workers